Kuwait : Selected Issues. (IMF Staff Country Reports; Country Report, 2011)
The expenditure multipliers in Kuwait are likely to be high, and mostly operate through capital expenditure. Kuwait's large state-controlled endowment of natural resource, pegged exchange rate regimes, and relatively open financial accounts are the mainstay. The nominal effective exchange rate diverged from the set pattern owing to higher inflation. Estimates from methodologies for exchange rate assessment indicate mixed results. Macroprudential policies in Kuwait would strengthen the management of systemic risk by reducing the probability and the impact of a financial boom-bust cycle on economic activity.